Analysis of literacy interest of early childhood 4-6 years in TKIT Azzahroh Kota Serang - Aprilyanti, Dian Surya; Rissani, Rissani; Verli, Verli (IKIP Siliwangi, 2024)
This study aims to describe the efforts made in increasing children’s interent in early childhood literacy at TKIT Azzahroh. The research method used is descriptive qualitative methode with data collection techniques through observation while teaching at TKIT Azzahroh, as wall as interviews with teachers and parent of student from TKIT Azzahoh. Literacy in early childhood is an important foundation for children’s cognitive and emotional development. Literacy that begins at an early age plays a role in shaping effective reading, writing and communication skills in the future. Through literarute review and field observation, it was found that literacy interventions that involve active interaction between children and adults, as well as the use of interestingreading materials, can increase children’s interest in reading and literacy skills. The results show that various strategies implemented by teacher and support from parent contribute significantly to improving children’s literacy interest. The findings are analyzed in the context of early childhood development theory and are expected to provide guidance for educators and parents in desingning effective literacy programsfor early childhooh